Critical Discourse Analysis in the Perception of European Union Media Discourse: Representations of Power, Crisis, and Identity - Salih, Rajaa Hamid (Forum for Linguistic Studies, 2025)
The aim of this article is to investigate how the European Union is represented in selected European media outlets using Critical Discourse Analysis (CDA) as a methodological basis. Specifically, the research draws on Norman Fairclough’s three-dimensional model and the Discursive-Historical Approach (DHA) to reveal how linguistic and discursive techniques contribute to shaping dominant narratives about the EU. Through a qualitative analysis of 30 news articles from five diverse media organizations within the EU, the study highlights that journalistic discourse not only reflects but also actively influences public perceptions of the Union. Three main themes emerge from the analysis: the portrayal of the EU as a fragmented and overly bureaucratic entity, often criticized for its inefficiency and democratic shortcomings; the dominance of a crisis-focused narrative that frames the EU primarily through the lens of political, economic, and social turmoil, reinforcing a sense of instability; and the expression of European identity is mediated through processes of inclusion and exclusion, whereby certain groups, values, or countries are either included in or excluded from the concept of Europeanness. The findings demonstrate how media narratives play a role in (re)creating power dynamics within the EU environment, positioning media outlets not only as passive conduits of information but as active ideological actors. The article highlights how critical discourse analysis reveals power dynamics in political and institutional language. Ultimately, the study offers insights into how discourse shapes and is shaped by larger sociopolitical developments, such as European integration, identity creation, and polarization within the EU.